Bovine colostral cells : the often forgotten component of colostrum - Gonzalez, Diego; Dus Santos, Maria Jose (American Veterinary Medical Association, 2019)
Because bovine maternal and fetal blood supplies are kept separate in utero, calves are immunologically naïve immediately after birth, which puts them at high risk for disease. The acquisition of passive immunity, generally through the ingestion of colostrum, helps protect calves against disease during this critical period. Cattle producers routinely feed newborn calves fresh (ie, never frozen) or frozen colostrum, which contains antibodies against pathogens within the local environment; however, antibodies are not the sole constituents of colostrum and passively acquired immunity. In addition to maternally derived antibodies, colostrum contains immunologically important cytokines and a large number of maternally derived (materBovine nal) leukocytes, which collectively contribute to the immunoprotection of the neonate.13–16 Although the role of colostral antibodies in the protection of neonates against disease has been well documented,17–20 the role of colostral cellular components in passive immunity is less well understood.21–28 In the early 1970s, researchers began to suggest that maternal lymphocytes in colostrum were primed antigen-responsive cells that, when ingested soon after birth, penetrate the permeable intestinal wall and provide transient local or systemic cell-mediated immunity, the breadth of which reflects the antigenic exposure of the cow from which the colostrum was acquired.